STRATEGI KOMUNIKASI KEMENTERIAN PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK UNTUK MENEKAN KASUS PERDAGANGAN PEREMPUAN - Virgitta Septyana (Universitas Bunda Mulia, 2013)
Human Trafficking is a modern form of human slavery and the worst form of violation of the human. In the case of trafficking in women, what happened is a violation of human rights, where women are treated merely as objects of exploitation, and the rights of victims are often harassed. Indonesia is primarily a source, but also a transit and destination country for human trafficking. There are many causes of human trafficking in Indonesia occurs widely, ranging from economic factors, low education, culture, and the lack of government oversight. Economic factors and education are considered to be the two dominant factor. One of the parties who responsible for taking action against cases of women trafficking is a Ministry of Women Empowerment and Childs. To suppress cases of women trafficking, the Ministry made a number communication plan. Those strategy is tailored to the factors causing the occurence of women trafficking, especially economic and education factors.Keywords: Human trafficking, Communication Strategy, Persuasion Technique